The Effect of Red Spinach Tea (Amaranthus Tricolor L) on Blood Profile in Adolescent Girls with Anemia - Annie Cristyana Purba; Sri Sumarni; Irmawati Irmawati (Indonesian Journal of Global Health Research, 2025)
Anemia continues to be a major nutritional problem in Indonesia, especially among school children and adolescents, which in turn can inhibit growth, reduce learning achievement, and weaken endurance due to reduced concentration and can cause complications during pregnancy, so researchers innovate in preventing these nutritional problems by providing Red Spinach Tea (Amaranthus Tricolor L) and Blood Addition Tablets. Analyzing the effect of Red Spinach Tea (Amaranthus Tricolor L) dose of 2 gr plus 60 mg fe tablets given once a day for 14 days on hemoglobin, hematocrit and erythrocyte levels in adolescent girls with anemia. True Experiment research with pretest-postest design with control group, consisting of 2 groups. The population was female students at Poltekkes Kemenkes Medan with the age of 17-19 years with a total sample of 20 respondents per group. The intervention was given a dose of red spinach tea 2 g given once a day for 14 days and 60 mg blood supplement tablets once a day for 14 days. Bivariate test for paired groups with non-normally distributed data using the Wilcoxon test. Bivariate tests for anpaired groups of pre and post data are not normally distributed, then use the Mann-Whitney test. It was found that the average hemoglobin, hematocrit and erythrocytes in adolescent girls in the intervention group with the administration of Red Spinach Tea and Blood Addition Tablets were higher than the control group with the consumption of Blood Addition Tablets. There is an effect of giving Red Spinach Tea and Blood Addition Tablets on increasing hemoglobin, hematocrit and erythrocyte levels in anemic adolescent girls with p-value = 0,000 (<0.05). Red Spinach Tea (Amaranthus Tricolor L) can potentially be used as a companion to blood supplement tablets to improve anemia status in adolescent girls. Thus, Red Spinach Tea can be utilized as an alternative to complementary therapy in preventing anemia.